Application of Phenomena Based-Interactive Conceptual Instruction (PB-ICI) to Foster Critical Thinking Skills and Spiritual Attitude - Johan, Henny; Mayub, Afrizal; Wardana, Rendy Wikrama; Noviana, Noni; Umaya, Umaya (Kasuari: Physics Education Journal (KPEJ), 2024)
Learning programmes need to be designed to provide cognitive aspects, especially critical thinking skills with indikators and aspects of spiritual attitudes in the learning process. This study aims to apply the Phenomena Based-Interactive Conceptual Instruction (PB-ICI) lecture model to equip critical thinking skills and instil spiritual values through science learning. This research uses a quasi-experiment. The results showed that the average pre-test score of critical thinking skills was 43.45 in the low category, the average post-test score was 79.48 in the high category and the average N-gain was 0.64 in the medium category. The results of the analysis of the cultivation of spiritual values show that PB-ICI learning can instil spiritual values related to the nature of divinity with an average response score of 88. Thus it is concluded that PB-ICI learning can improve critical thinking, instil spiritual values and get a very good response after PB-ICI learning implementation activities.